Consistency in Aggregation of GDP Indexes and Uniqueness of Quantity and Price Effects on Growth of GDP and Aggregate Labor Productivity - Dumagan, Jesus C. (Animo Repository, 2017)
In traditional decomposition of GDP growth in constant prices, an industry’s contribution consisted only of a quantity effect from GDP growth. Tang and Wang’s (2004, 2014) innovation added a price effect from relative price change. Dumagan (2013a, 2016) showed that Tang and Wang’s quantity and price effects for all industries exactly add up to growth of GDP either in chained or in constant prices, that is, regardless of the GDP index. However, this paper shows that it is only when GDP is in chained prices and the GDP index is consistent-in-aggregation (CIA) that quantity and price effects are invariant with industry regroupings, that is, unique. Therefore, Tang and Wang’s (2004, 2014) growth decompositions in Canada and US—where GDP is in chained prices based on the Fisher index—yield effects that vary with industry regroupings because the Fisher index is not CIA. This variation prevents attributing unique price and quantity effects to industries and, thus, clouds Tang and Wang’s analysis of the role of industries in GDP growth and in aggregate labor productivity growth. This paper also examines price and quantity effects on GDP growth of representative countries with GDP different from that in the US to make the results globally relevant.